Three‐year surveillance (2016–2018) of chigger mites vector for tsutsugamushi disease in the Hwaseong‐Si area of Gyeonggi‐Do, Republic of Korea. Issue 2 (22nd December 2019) - Jun, Hojong; Jegal, Seung; Kim‐Jeon, Myung‐Deok; Roh, Jong Yul; Lee, Wook‐Gyo; Park, Seo Hye; Ahn, Seong Kyu; Lee, Jinyoung; Gong, Young Woo; Kwon, Mun Ju; Bahk, Young Yil; Kim, Tong‐Soo
Abstract: Owing to climate change, the global resurgence of vector‐borne infectious diseases has emerged as a critical public health issue. Orientia tsutsugamushi is the etiological agent of tsutsugamushi disease (scrub typhus) a mite‐borne acute febrile disease occurring in the Asia‐Pacific region. We investigated the prevalence of tsutsugamushi disease transmitted by chigger mite vectors living on rodents. Using sticky‐type chigger traps for three months during 2016–2018, 1, 057 chigger mites were collected (chigger mite index, 1.31) from four locations in the Hwaseong‐si area of Gyeonggi‐do, Republic of Korea. Five species distributed among three genera were identified. In addition, 94 rodents were captured (collection rate: 7.83%) using Sherman live traps over the course of three months (April, October, and November) during 2016–2017. Three rodent species were captured and identified and the striped field mouse ( Apodemus agrarius ) was the dominant rodent host species in the surveyed area. A total of 10, 469 ectoparasitic chigger mites were recovered from the 94 rodents, from which 13 species distributed among four genera were identified. Of the 5, 250 chigger mites examined, Leptotrombidium pallidum was most abundant (n = 2, 558), followed by L. orientale, L. scutellare, L. zetum, Euschoengastia koreaensis, L. subintermedium, and Neotrombicula tamiyai . Of the examined chigger mites, no groups recovered from rodent hosts tested positive for O. tsutsugamushi . This study provides fundamental regional information on vector‐borne disease data collection in the Hwaseong‐si area, Gyeonggi‐do, and will further contribute to formulating disease control and prevention strategies.